Menilai Efektivitas Peraturan Larangan Perjudian dalam Daerah: Studi Atas Perda Sambas Nomor 4 Tahun 2004 - Tamrin, Tamrin; Saliro, Sri Sudono; Septemberiadi, Lando (AL-SULTHANIYAH, 2025)
This study aims to answer the research problem: how is the Effectiveness of the Implementation of Regional Regulation of Sambas Regency Number 4 of 2004 Concerning the Prohibition of Gambling in the Region? What is the Position of Regional Regulation No. 4 of 2004 in the Hierarchy of legislation. The research method is qualitative, with the type of field research and using an empirical legal approach. The results reveal that Sambas Regional Regulation No. 4 of 2004 is not running effectively and cannot be applied to ensnare criminal acts of gambling in the region. Currently, the application of criminal acts of gambling in Sambas Regency applies Article 301 of the Criminal Code. While the position of Regional Regulation No. 4 of 2004 in the hierarchy of legislation is below the Law. The consequence of this is that the Regional Regulation in question is contrary to the Criminal Code as a Law in terms of the content of Gambling and has an impact on the implementation of the Regional Regulation which in reality, the Regional Regulation has never been used to ensnare Gamblers, so the Regional Regulation should be null and void by law. So to create the principle of legal certainty, Regional Regulation No. 4 of 2004 must be revoked by using Regional Regulations as well.